A virtual Environment Interface to Compare Autonomous Perceptual Systems - Caudell, Thomas P. (International Journal of Virtual Reality, 1995)
This paper describes the on-going development of a novel interface approach to understanding complex systems. We present a description of an interface, referred to as a Homunculus, which allows an experimenter to explore complex systems through immersive virtual reality technology. We describe an initial application under development where the Encephalon, a biologically motivated neural architecture, is used to control a robotics system. Encephalon modules are represented in the Homunculus as 3D icons. Information flow between modules of the neural network is represented as graphical animations. Virtual tools will be available to view, manipulate, model, diagnose, analyze, and navigate through the software and multi-dimensional data. We discuss many important research questions revealed by this work.